Integrated effect of allelochemicals and herbicides on weed suppression and soil microbial activity in wheat (Triticum aestivum L.). (December 2016) - Khan, Muhammad Azim; Afridi, Riaz Ahmad; Hashim, Saima; Khattak, Abdul Mateen; Ahmad, Zubair; Wahid, Fazli; Chauhan, Bhagirath Singh
Abstract: To evaluate the allelopathic effects of major crops and weeds, studies were conducted during 2011–12 and 2012–13 by utilizing water extracts of allelopathic plants namely rice ( Oryza sativa L.), Parthenium hysterophorus L., Phragmites australis Cav., and Datura alba L. with reduced rates of fenoxaprop- p -ethyl and bromoxynil plus MCPA to control weeds. Application of Phragmites australis and Parthenium hysterophorus along with lower rates of fenoxaprop- p -ethyl and bromoxynil plus MCPA showed promising results by controlling weeds and improving yield. Parthenium hysterophorus extract with half of the recommended dose of fenoxaprop- p -ethyl and bromoxynil plus MCPA reduced weed density by 51 and 50% during year 1 and year 2, respectively, compared with the control. Phragmites australis extract with half of the recommended dose of fenoxaprop- p -ethyl produced grain yield (5.7 and 6.1 t ha −1 during year 1 and 2, respectively) in wheat. However, these results were also at par with Parthenium hysterophorus and Datura alba extracts in combinations with half the recommended doses of the above mentioned herbicides. The study of microbial activity showed higher amount of mineralizable carbon in D . alba with half the recommended dose of fenoxaprop- p -ethyl treated plots (0.073 g during both the years). The lowest amount of mineralizable carbon (0.035 and 0.030 g during year 1 and 2, respectively) was observed in the control plots. The presence of allelopathic plants in field crops and subsequent mixing in soil by tillage may create problems in crop production. Therefore, further studies are suggested to fully explore all the possible interactions among allelochemicals and herbicides. Highlights: Allelochemicals and herbicides effect on weeds, and microbial activity was studied. Aqueous extracts of different allelopathic plant species suppressed weeds effectively. Combination of extracts with reduced herbicides' doses increased wheat grain yield. Allelochemicals with reduced herbicide applications can be used in weed management.